2021
DOI: 10.3389/fcvm.2021.774781
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Triglyceride-Glucose Index for Adverse Cardiovascular Events in Patients With Coronary Artery Disease: A Systematic Review and Meta-Analysis

Abstract: Background: Insulin resistance (IR) represents a critical regulator in the development and progress of coronary artery disease (CAD). Triglyceride-glucose (TyG) index, a novel surrogate biomarker of IR, has been implicated in several cardiovascular diseases. Accordingly, we conduct a meta-analysis to elucidate the relationship between TyG index and adverse cardiovascular events in patients with CAD.Methods: To identify the studies examining the predictive capacity of the TyG index for adverse cardiovascular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…The triglyceride-glucose (TyG) index, calculated as ln (fasting triglycerides (mg/dl) × fasting blood glucose (mg/dl)/2), has become a valuable biomarker for insulin resistance [3]. Previous studies have shown that the TyG index was associated with cardiovascular events [4]. For instance, the TyG index was associated with the prevalence of coronary artery disease (CAD) [5] and an increased risk of ischemic stroke [6], hypertension [7], and arterial stiffness [8].…”
Section: Introductionmentioning
confidence: 99%
“…The triglyceride-glucose (TyG) index, calculated as ln (fasting triglycerides (mg/dl) × fasting blood glucose (mg/dl)/2), has become a valuable biomarker for insulin resistance [3]. Previous studies have shown that the TyG index was associated with cardiovascular events [4]. For instance, the TyG index was associated with the prevalence of coronary artery disease (CAD) [5] and an increased risk of ischemic stroke [6], hypertension [7], and arterial stiffness [8].…”
Section: Introductionmentioning
confidence: 99%
“…In some aspects, TyG is even more effective than the HOMA-IR model, especially in predicting metabolic syndrome, and arterial stiffness [7,8]. And several studies have demonstrated that the TyG index can predict myocardial infarction, stroke or other adverse cardiovascular events [9][10][11]. However, no studies have investigated the relationship between the TyG index and cardiovascular events in CTO patients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the serum levels of glucose and triglyceride, we identified that the TyG index was a predictor of 6-month readmission in HF patients. The elevated TyG index is a predictive factor of adverse cardiovascular events in myocardial infarction with nonobstructive coronary arteries [ 14 ], coronary artery disease [ 8 ], hypertension [ 7 ], and chronic heart failure [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the triglyceride glucose (TyG) index was confirmed to be a surrogate marker of insulin resistance [ 6 ]. Previous studies demonstrated that TyG index was of prognostic value in patients with hypertension [ 7 ], coronary artery disease [ 8 ], or heart failure [ 9 ]. In addition, TyG was a novel biomarker of myocardial fibrosis in HF patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%